An Improved Scalable Synthesis of the Potent Antiviral (S)‐HPMPA. Issue 11 (28th November 2022) - Kumar, Racherla Kishore; Sanghvi, Yogesh S.; Reddy, Paidi Yella; Banerjee, Shyamapada
Abstract: We present an improved synthesis of ( S )‐HPMPA (1 ) from an easily accessible and commercially available compound, ( S )‐3‐(benzyloxy)propane‐1, 2‐diol (10 ). Tritylation of primary alcohol 10 was highly selective, and pure product was isolated in good yield. Alkylation of ( R )‐1‐(benzyloxy)‐3‐(trityloxy)propan‐2‐ol (11 ) with diethyl p ‐toluenesulfonyloxymethyl phosphonate (6 ) using sodium hydride in tetrahydrofuran followed by detritylation afforded the desired chiral synthon 12 . Tosylation of the primary alcohol and subsequent reaction with sodium adeninate afforded protected S ‐HPMPA (14 ). Global deprotection using concentrated hydrochloric acid in a sealed tube afforded S ‐HPMA (1 ), and the deprotected 1 was crystallized from water and acetone to obtain a 99% pure product. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of ( R )‐1‐(benzyloxy)‐3‐(trityloxy)propan‐2‐ol (11 ) Basic Protocol 2 : Preparation of diethyl ( S )‐(((1‐(benzyloxy)‐3‐hydroxypropan‐2‐yl)oxy)methyl)phosphonate (12 ) Basic Protocol 3 : Preparation of ( R )‐3‐(benzyloxy)‐2‐((diethoxyphosphoryl)methoxy)propyl‐4‐methylbenzenesulfonate (13 ) Basic Protocol 4 : Preparation of diethyl ( S )‐(((1‐(6‐amino‐9 H ‐purin‐9‐yl)‐3‐(benzyloxy)propan‐2‐yl)oxy)methyl)phosphonate (14 ) Support Protocol 1 : Preparation of sodium adeninate Basic Protocol 5 : Preparation of ( S )‐(((1‐(6‐amino‐9 H ‐purin‐9‐yl)‐3‐hydroxypropan‐2‐yl)oxy)methyl)phosphonic acid (1 )